Evidence of arsenic release promoted by disinfection by-products within drinking-water distribution systems - Andra, Syam S.; Makris, Konstantinos C.; Costa, Costas; Charisiadis, Pantelis; Botsaris, George (My University, 2014)
Changes in disinfectant type could trigger a cascade of reactions releasing pipe-anchored metals/metalloids into finished water. However, the effect of pre-formed disinfection by-products on the release of sorbed contaminants (arsenic-As in particular) from drinking water distribution system pipe scales remains unexplored. A bench-scale study using a factorial experimental design was performed to evaluate the independent and interaction effects of trihalomethanes (TTHM) and haloacetic acids (HAA) on arsenic (As) release from either scales-only or scale-biofilm conglomerates (SBC) both anchored on asbestos/cement pipe coupons. A model biofilm (Pseudomonas aeruginosa) was allowed to grow on select pipe coupons prior experimentation. Either TTHM or HAA individual dosing did not promote As release from either scales only or SBC, detecting < 6 μg As L− 1 in finished water. In the case of scales-only coupons, the combination of the highest spike level of TTHM and HAA significantly (p < 0.001) increased dissolved and total As concentrations to levels up to 16 and 95 μg L− 1, respectively. Similar treatments in the presence of biofilm (SBC) resulted in significant (p < 0.001) increase in dissolved and total recoverable As up to 20 and 47 μg L− 1, respectively, exceeding the regulatory As limit. Whether or not, our laboratory-based results truly represent mechanisms operating in disinfected finished water in pipe networks remains to be investigated in the field.
Keywords: Arsenic; Biofilm; Disinfection by-products; Pipe scales; Drinking water distribution system; Water and health